Autobiographical memory of war veterans: A mixed-studies systematic review. (April 2021) - Islam, Azharul; Sheppard, Elizabeth; Conway, Martin A; Haque, Shamsul
This paper reviewed articles on autobiographical memories of veterans who fought several major battles around the world. A total of 28 articles, reporting 11 quantitative, 16 qualitative, and 1 mixed-methods study, were identified through a search conducted in 11 major databases. Convergent thematic analysis of the findings extracted five recurrent themes: (1) memory features, (2) memory content, (3) self and memory, (4) culture and memory, and (5) theoretical accounts. Veterans' memories were mostly aligned with the hegemonic narratives, although many of them were the depiction of atrocities (theme 1). Veterans with post-traumatic stress disorder and other mental disorders recalled less specific and less coherent autobiographical memories (theme 2); their retrieval was influenced by split identity—combatant versus veteran identity, generational identity, and political ideology (theme 3). War outcome, dominant public narratives, political environment, and myths prevailing in the society influenced the memory recall (theme 4). While qualitative studies used Erickson's identity theory to explain how personal identity in conjunction with social identity helped to construct veterans' memories, quantitative studies used Car-Fa-X model to explain why veterans with various mental health conditions predominantly produced overgeneral memories (theme 5). Findings are discussed through the current theories of autobiographical memory.